Proceedings of the International Symposium on Performance Science 2013 - Williamon, Aaron; Goebl, Werner (Utrecht European Association of Conservatoires (AEC), 2013)
The ISPS 2013 theme, Performing Together, is intended to encourage discussion and debate on collaborative performing activities of all types and between various constituents.